Critical Ecolinguistics Analysis on Tourism Brochure Translation: From Nature Appreciation to Adventure Consumption (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
This study critically examines the tourism brochure of West Kotawaringin, Central Kalimantan, Indonesia, from Indonesian to English. It argues that the translator’s choice of strategies reshapes the region's ecological and cultural landscape in the target text. Employing Venuti’s domestication and foreignization strategies as well as Stibbe’s ecolinguistics framework, the analysis reveals shifts from narratives that encourage genuine nature appreciation to those promoting adventure consumption, thereby reinforcing an inherently anthropocentric worldview. Key findings unequivocally highlight a significant erasure of indigenous eco-technologies and local knowledge, exemplified by the generic rendering of terms like kelotok and perahu getek into simply “a boat,” and the mistranslation of the culturally vital sumpit (blowpipe) as “chopstick”. This linguistic simplification and misrepresentation contribute to the commodification of the region, framing it through an exotic-romantic imaginary that obscures its identity and complex socio-ecological realities. Furthermore, factual inaccuracies, such as the incorrect conversion of “hectares” to “acres,” disrupt narrative conviction and contribute to the institutionalization of natural spaces, presenting them as managed facilities rather than holistic ecosystems. The predominant reliance on domestication strategies effectively silences the environment, replacing rich, interconnected stories with a simplified, consumer-oriented discourse. This research critically underscores the urgent need for ethically and ecologically conscious approaches to tourism translation that actively resist anthropocentric biases, foster authentic representation, and ultimately promote genuine eco-cultural sustainability in promotional materials.